Jerzy Grobicki (1891–1972). From the Foreign Legion to the Polish Army General. A Cavalryman’s Biography - Dubicki, Tadeusz (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article discusses the figure of Jerzy Grobicki (1891–1972) who served as an officer of the imperial and royal army and became the Polish Army colonel in the Second Polish Republic. He participated in World Wars I and II and after the war migrated to Canada.